Epithelial Cyst in the Posterior Triangle of the Neck: Atypical Branchial Cyst or Cystic Lymph Node Metastasis?. (12th January 2014) - Vital, Domenic; Huber, Gerhard F.; Pézier, Thomas F.; Rössle, Matthias; Probst, Rudolf; Widmer, Gian-Marco
Abstract : We report the case of a 66-year-old man with a cervical neck mass located behind the left sternocleidomastoid muscle. To exclude malignancy, a full workup, including clinical, radiological, and cytological examination, was performed but failed to provide a definitive diagnosis. Histological analysis following excisional biopsy revealed a benign epithelial cyst, consistent with an atypically located branchial cyst. We describe an approach to the management of these neck masses and discuss several theories of the etiology of branchial cysts and how they may come to be abnormally located.